Old-loofah-derived hard carbon for long cyclicity anode in sodium ion battery. (8th February 2018) - Yu, Chengyi; Hou, Hongying; Liu, Xianxi; Yao, Yuan; Liao, Qishu; Dai, Zhipeng; Li, Dongdong
Abstract: Hard carbon was prepared via the carbonization of the old loofah sponge at 800 °C for 1 h in the inert N2 atmosphere for sodium ion battery (SIB) anode. The resultant old-loofah-derived hard carbon was investigated by scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray photoelectron spectroscopy (XPS), Raman, galvanostatic charge/discharge, cyclic voltammetry (CV) and alternating current (AC) impedance. The results suggested that the old-loofah-derived hard carbon powders consisted of many irregular micro-particles with the mean particle size of 12 μm. Furthermore, the old-loofah-derived hard carbon anode also delivered satisfactory electrochemical performances in SIB. For example, the initial discharge specific capacity was as high as about 695 mAh g −1 at 25 mA g −1, and the reversible discharge specific capability after 1000 cycles was still about 171 mAh g −1 even at 1000 mA g −1, indicating long cycle stability and the promising feasibility of the old-loofah-derived hard carbon anode. The disordered micro-structure and large interlayer distance may jointly contribute into the satisfactory electrochemical performances. Highlights: The old loofah sponge was carbonized at 800 °C under the inert atmosphere. The feasibility of the old loofah derived hard carbon as SIB anode was studied. The obtained hard carbon anode delivered long cycle life in SIB. The new connection between the old loofah and SIB anode was built.